Measurement and Control of Charged Particle Beams - Minty, Michiko G. (Particle Acceleration and Detection, 2003)
This advanced textbook and reference is the first comprehensive and systematic review of all methods used for the measurement, correction, and control of the beam dynamics of modern particle accelerators. Based on material presented in several lectures at the US Particle Accelerator School, the text is intended for graduate students starting research or work in the field of beam physics. Relativistic beams in linear accelerators and storage rings provide the focus. After a review of linear optics, the text addresses basic and advanced techniques for beam control, plus a variety of methods for the manipulation of particle-beam properties. In each case, specific procedures are illustrated by examples from operational accelerators, e.g., CERN, DESY, SLAC, KEK, LBNL, and FNAL. The book also treats special topics such as injection and extraction methods, beam cooling, spin transport, and polarization. Problems and solutions enhance the book's usefulness in graduate courses.